2016
DOI: 10.1109/tvcg.2015.2467198
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Interactive Visualization of Large Deformations and Variability in Biomedical Image Ensembles

Abstract: Large image deformations pose a challenging problem for the visualization and statistical analysis of 3D image ensembles which have a multitude of applications in biology and medicine. Simple linear interpolation in the tangent space of the ensemble introduces artifactual anatomical structures that hamper the application of targeted visual shape analysis techniques. In this work we make use of the theory of stationary velocity fields to facilitate interactive non-linear image interpolation and plausible extrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…With respect to the quantification and exploration of the organ shape variation, Hermann et al [HSSK16] covered the topic of visualization of anatomic covariances in ensembles of data. They also published a state of the art report with future prospects on the visual analysis of shapes [HK15], which we took into consideration during the design phase of the Bladder Runner.…”
Section: Related Workmentioning
confidence: 99%
“…With respect to the quantification and exploration of the organ shape variation, Hermann et al [HSSK16] covered the topic of visualization of anatomic covariances in ensembles of data. They also published a state of the art report with future prospects on the visual analysis of shapes [HK15], which we took into consideration during the design phase of the Bladder Runner.…”
Section: Related Workmentioning
confidence: 99%
“…In shape space analysis, Hermann et al [27,28,29] investigate anatomic covariances in ensembles of data, providing also a state of the art report with prospects on the visual analysis of shapes [30]. Busking et al [31] propose to use a 2D scatter plot to represent the distribution of elements inside a cohort and to synthesize additional arbitrary objects in the shape space.…”
mentioning
confidence: 99%
“…A common theme in research on medical imaging and visualization are techniques for spatial comparison of 3D data, which may also be time-varying, i.e., spatio-temporal. Hermann et al [28] demonstrated how image warping can be used to show variability in ensembles of biomedical images and Raidou et al [50] proposed a tool for visual exploration of bladder shape variation during prostate cancer radiotherapy. Another approach is to merge data captured at different time steps to, for example, display a static overview, allowing direct comparison [21].…”
Section: Depicting Simulation Resultsmentioning
confidence: 99%